Development and Validation of a Clinical Score for Cardiovascular Risk Stratification of Long‐Term Childhood Cancer Survivors. (30th March 2018) - Oikonomou, Evangelos K.; Athanasopoulou, Sofia G.; Kampaktsis, Polydoros N.; Kokkinidis, Damianos G.; Papanastasiou, Christos A.; Feher, Attila; Steingart, Richard M.; Oeffinger, Kevin C.; Gupta, Dipti
Abstract : Background: Long‐term childhood cancer survivors (CCS) are at increased risk of adverse cardiovascular events; however, there is a paucity of risk‐stratification tools to identify those at higher‐than‐normal risk. Subjects, Materials, and Methods: This was a population‐based study using data from the Surveillance, Epidemiology, and End Results Program (1973–2013). Long‐term CCS (age at diagnosis ≤19 years, survival ≥5 years) were followed up over a median time period of 12.3 (5–40.9) years. Independent predictors of cardiovascular mortality (CVM) were combined into a risk score, which was developed in a derivation set ( n  = 22, 374), and validated in separate patient registries ( n  = 6, 437). Results: In the derivation registries, older age at diagnosis (≥10 years vs. reference group of 1–5 years), male sex, non‐white race, a history of lymphoma, and a history of radiation were independently associated with an increased risk of CVM among long‐term CCS ( p  < .05). A risk score derived from this model (Childhood and Adolescence Cancer Survivor CardioVascular score [CHACS‐CV], range: 0–8) showed good discrimination for CVM (Harrell's C‐index [95% confidence interval (CI)]: 0.73 [0.68–0.78], p  < .001) and identified a high‐risk group (CHACS‐CV ≥6), with cumulative CVM incidence over 30 years of 6.0% (95% CI: 4.3%–8.1%) versus 2.6% (95% CI: 1.8%–3.7%), and 0.7% (95% CI: 0.5%–1.0%) in the mid‐ (CHACS‐CV = 4–5) and low‐risk groups (CHACS‐CV ≤3), respectively ( p log‐rank  < .001). In the validation set, the respective cumulative incidence rates were 4.7%, 3.1%, and 0.8% ( p log‐rank  < .001). Conclusion: We propose a simple risk score that can be applied in everyday clinical practice to identify long‐term CCS at increased cardiovascular risk, who may benefit from early cardiovascular screening, and risk‐reduction strategies. Implications for Practice: Childhood cancer survivors (CCS) are known to be at increased cardiovascular risk. Currently available prognostic tools focus on treatment‐related adverse events and late development of congestive heart failure, but there is no prognostic model to date to estimate the risk of cardiovascular mortality among long‐term CCS. A simple clinical tool is proposed for cardiovascular risk stratification of long‐term CCS based on easily obtainable information from their medical history. This scoring system may be used as a first‐line screening tool to assist health care providers in identifying those who may benefit from closer follow‐up and enable timely deployment of preventive strategies. Abstract : This article focuses on the challenge of maintaining cardiovascular health in long‐term childhood cancer survivors. A simple risk score is proposed, which can be used in clinical practice to identify patients at increased cardiovascular risk.